2015
DOI: 10.14494/jnrs.15.1_1
|View full text |Cite
|
Sign up to set email alerts
|

Pu Distribution in Seawater in the Near Coastal Area off Fukushima after the Fukushima Daiichi Nuclear Power Plant Accident

Abstract: The Fukushima Daiichi Nuclear Power Plant (FDNPP) accident released large amount of radionuclides into the marine environment. Compared with the fission products, data on the distributions of Pu in the marine environment of the western North Pacific after the accident is limited. To better understand the Pu contamination in the marine environment after the accident, for the first time, we determined Pu isotope ratio ( 240 Pu/ 239 Pu) in addition to 239+240 Pu activity in seawater collected in the near coastal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The 239+240 Pu activity concentrations of the zone of >400 km from the FDNPP in this study (1.21–2.19 mBq/m 3 ) was typically in the range of the background data of the Northwest Pacific (Fig. 6 ) 18 , 19 , 24 , 46 , indicating negligible Pu contamination from the accident.
Figure 6 Comparison of 239+240 Pu activities in this study with the historical 239+240 Pu data in surface seawater of the Western North Pacific.
…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…The 239+240 Pu activity concentrations of the zone of >400 km from the FDNPP in this study (1.21–2.19 mBq/m 3 ) was typically in the range of the background data of the Northwest Pacific (Fig. 6 ) 18 , 19 , 24 , 46 , indicating negligible Pu contamination from the accident.
Figure 6 Comparison of 239+240 Pu activities in this study with the historical 239+240 Pu data in surface seawater of the Western North Pacific.
…”
Section: Resultssupporting
confidence: 49%
“…After the FDNPP accident, 239+240 Pu activity concentrations and 240 Pu/ 239 Pu atom ratios in seawater of Northwest Pacific were investigated to study if there was significant impact for Pu isotopes in seawater before and after the FDNPP accident. The seawater zone of <30 km, 30–200 km and >200 km off FDNNP were investigated respectively 19 , 24 , 38 40 . Their results suggested no significant Pu contamination from the accident in these areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of Chernobyl-derived Pu was confirmed to be negligible in the North Pacific Ocean 34 . The atomic ratios of 241 Pu/ 239 Pu and 240 Pu/ 239 Pu in seawater and marine sediments suggested that the Pu signal from the immediate impact and atmospheric deposition from the FNA was minor in the Pacific Ocean 12,16,18,[35][36][37]…”
Section: Resultsmentioning
confidence: 99%
“…However, the vertical structure of the 239+240 Pu inventory remains unclear. Furthermore, it was suggested that the 2011 Fukushima Nuclear Accident (FNA) exerted no immediate Pu impact on the northwestern Pacific Ocean 12,[15][16][17][18][19] . Overall, the limited available Pu data usually cover a local area, and therefore cannot yield unbiased interpretation for the Pacific Ocean as a whole.…”
Section: Introductionmentioning
confidence: 99%